A Tree-Structured Deterministic Small-World Network - GUO, Shi-Ze; LU, Zhe-Ming; KANG, Guang-Yu; LUO, Hao; CHEN, Zhe (IEICE Transactions on Information and Systems, 2012)
Small-world is a common property existing in many real-life social, technological and biological networks. Small-world networks distinguish themselves from others by their high clustering coefficient and short average path length. In the past dozen years, many probabilistic small-world networks and some deterministic small-world networks have been proposed utilizing various mechanisms. In this Letter, we propose a new deterministic small-world network model by first constructing a binary-tree structure and then adding links between each pair of brother nodes and links between each grandfather node and its four grandson nodes. Furthermore, we give the analytic solutions to several topological characteristics, which shows that the proposed model is a small-world network.